Spatialities of data: mapping social media 'beyond the geotag' - Shelton, Taylor (GeoJournal, 2017)
As emerging sources of so-called 'big data' are increasingly utilized in order to understand social and spatial processes, so too have these new data sources become the subject of harsh criticism from more critically-oriented geographers and social scientists. This paper argues that one of the major issues preventing a more productive dialogue between critical human geographers and those already engaging in the mapping and analysis of these new data sources is around the ways that space and spatiality are conceptualized in social media mapping. As such, this paper draws on and extends earlier critiques of the 'spatial ontology of the geotag', in which the geographic analysis of geotagged social media data overprivileges the single latitude/longitude coordinate pair attached to each individual data point, often leading to the kind of simplistic mappings and interpretations prevalent today. The goals of this paper are two-fold: first, to demonstrate how the spatial ontology of the geotag is implicitly operationalized within mainstream social media mapping exercises, and how this understanding of space remains incongruent with existing conceptions of space drawn from human geography. Second, using the example of tweeting in the wake of the August 2014 killing of an unarmed African-American teenager by a police officer in Ferguson, Missouri, this paper demonstrates how a more geographically-situated analysis of this kind of data, inspired by relational or multidimensional conceptualizations of space, can yield alternative understandings of the social processes embedded in such data.